Motives of consumption of paid physical culture and health services for the adult population (gender aspect) - P. V. Pasechnik; N. V. Filonenko (Путеводитель предпринимателя, 2020)
This article deals with the problem, in particular the gender aspect, of the motivational factors of consumption when choosing paid physical culture and health services for adults, the results of a questionnaire of men and women of 30-59 years are given separately, conclusions of a recommendatory nature are presented.